América Central: situación migratoria después de los conflictos - Cecilia Olmos (Les Cahiers ALHIM)
This paper analyses the political conflicts in three Central American countries: Nicaragua, El Salvador and Guatemala as well as the migratory process that was created as a result of the politically forced displacement of populations and how it affects two countries, Mexico and the United States. Through the years the structural form of this migration has been modified inducing a change in the immigration laws and the aid given to refugees. Undocumented migrants, a majority of the displaced population, are more likely to be deported from the countries where they hope to find refuge.